Review and Analysis of mental health reforms in several countries: Implementation, comparison and future challenges - Avital Alfandari Cohen; Racheli Magnezi; Orly Weinstein (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
Mental health disorders affect people in all societies. In the past thirty years, countries have launched mental health program reforms to care for people affected by mental disorders, mental well-being and protection of human rights. This review presents a wide range of mental health reforms conducted in different countries, compares barriers, present trends for the future and highlight what can be learned from them. A literature review using Pubmed, Ebsco, world bank.org, OECD, Statistic Times and the WHO Mental Health Atlases for 2001, 2005, 2011, and 2017 databases was conducted.  The results are presented in tables highlighting key elements comparing demographic information, healthcare professionals working in the mental health sector, policies, legislation and site of treatment in 19 countries. Crucial information is presented in four main themes: Legislation and Regulations; Mental health policies, plans and programs; Eliminating the custodial approach and stigma; and Deinstitutionalization/priority on community care and networks of care.  Most mental health reforms began with deinstitutionalization without fully considering the infrastructure needed for community care, financing and the number of healthcare workers in the mental health sector. When initiating mental health reform policy makers should consider legislation, financial ability and establishing intermediate community services to facilitate rehabilitation.